Uncovered return parity: Equity returns and currency returns - Edouard Djeutem; Geoffrey R. Dunbar (Bank of Canada, 2018)
We propose an uncovered expected returns parity (URP) condition for the bilateral spot exchange rate. URP implies that unilateral exchange rate equations are misspecified and that equity returns also affect exchange rates. Fama regressions provide evidence that URP is statistically preferred to uncovered interest rate parity (UIP) for nominal bilateral exchange rates between the US dollar and six countries (Australia, Canada, Japan, Norway, Switzerland and the UK) at the monthly frequency. An implication of URP is that commodity price changes that affect equity returns thus affect bilateral exchange rates through the equity channel. We find evidence that the Australian, Canadian, Norwegian (post 2001) and UK (post 1992) expected exchange rates increase via the oil-equity channel as oil prices rise, whereas the Japanese and Swiss expected exchange rates decrease.
Keywords: E43; F31; G15; 330; Asset pricing; Exchange rates; International financial markets